2018
DOI: 10.1136/jnnp-2018-abn.121
|View full text |Cite
|
Sign up to set email alerts
|

WED 241 Clinical relevance of regular blood monitoring in IG treatment

Abstract: BackgroundABN immunoglobulin (Ig) guidelines advise routine FBC and U and E monitoring with every treatment episode and screening for IgA deficiency. AimsWe audited compliance in inflammatory neuropathy patients on longterm treatment in two UK Neurology departments. We looked for evidence of clinically relevant haematological or AKI Ig-related events.MethodsData was collected from Nov 2015 to Nov 2017. Accepted definitions for clinically and/or biochemically significant haemolysis, neutropenia, thrombocytopeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is conflicting evidence about whether the risk of developing these side effects correlates with dose of IVIg. Rajabally et al reported that a daily dose greater than 35g of IVIg resulted in a higher risk of thrombotic events and another large retrospective, UK study found clinically significant Ig-related haemolysis occurred in association with induction bolus doses only (34,35). The same study revealed Ig-related biochemical changes in haemoglobin and sodium without clinical effect occurred more commonly in individual with low pre-treatment haemoglobin or those on concomitant medication which can contribute to hyponatraemia (35).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is conflicting evidence about whether the risk of developing these side effects correlates with dose of IVIg. Rajabally et al reported that a daily dose greater than 35g of IVIg resulted in a higher risk of thrombotic events and another large retrospective, UK study found clinically significant Ig-related haemolysis occurred in association with induction bolus doses only (34,35). The same study revealed Ig-related biochemical changes in haemoglobin and sodium without clinical effect occurred more commonly in individual with low pre-treatment haemoglobin or those on concomitant medication which can contribute to hyponatraemia (35).…”
Section: Discussionmentioning
confidence: 96%
“…Rajabally et al reported that a daily dose greater than 35g of IVIg resulted in a higher risk of thrombotic events and another large retrospective, UK study found clinically significant Ig-related haemolysis occurred in association with induction bolus doses only (34,35). The same study revealed Ig-related biochemical changes in haemoglobin and sodium without clinical effect occurred more commonly in individual with low pre-treatment haemoglobin or those on concomitant medication which can contribute to hyponatraemia (35). A study in our neuromuscular cohort did not find a difference in IVIg doses between the group of patients experiencing a thromboembolic event and those who did not (34,36).…”
Section: Discussionmentioning
confidence: 99%